Microwave-assisted biosynthesis of C12A7 nanopowders from Aloe Vera leaf extract - Waramon LANGLAR; Areeya AEIMBHU; Pichet LIMSUWAN; Chesta RUTTANAPUN (My University, 2020)
In this paper, the synthesis of C12A7 nanopowders with OH− specie inside cage via biological method using Aloe Vera (A. vera) leaf extract with different concentrations of 0, 15, 20, 25 and 50%, and microwave-assisted synthesis was reported. The effects of A. vera leaf extract concentration on the structure, morphology and specific surface area of C12A7 nanopowders were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy and N2 gas adsorption–desorption isotherm, respectively. The functional groups of C12A7 nanopowders with OH− specie inside cage were analyzed by fourier transform infrared spectroscopy (FT-IR). The XRD patterns showed that the pure peak of C12A7 was obtained from the samples prepared with A. vera leaf extract concentration of 20% and above. The minimum crystallite size of the C12A7 nanopowders was found to be 43.17 nm for the sample prepared with 25% A. vera leaf extract concentration. The maximum specific surface area (SBET) obtained from N2 gas adsorption–desorption isotherm was found to be 17.25 m2/g with a minimum pore size of 12.24 nm for the sample prepared with 25% A. vera leaf extract concentration. The FT-IR spectra of C12A7 prepared with A. vera leaf extract reveals the presence of amide of protein in A. vera leaf bonded to C12A7 indicating the biological responsibility for the synthesis of C12A7. Furthermore, in this work with the microwave-assisted synthesis of C12A7 nanopowders, the calcining time could be reduced by 10 h compared with a chemical process and temperature could be reduced to 900 °C compared with a standard sintering temperature.
Keywords: Aloe Vera; Phytochemistry and biological activity of medicinal plants